Composite coating for improving surface performance of carbon-based electrode, graphite electrode and preparation method

The preparation of Ta-TaxC-TaC composite coating through magnetron sputtering and double-ray plasma surface metallurgy technology solves the problem of easy oxidation and ablation of graphite electrodes at high temperatures, and achieves efficient ablation and oxidation resistance, which extends the The service life is reduced and the preparation cost is reduced.

CN115404452BActive Publication Date: 2025-01-03NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210906320.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-29
Publication Date
2025-01-03
Estimated Expiration
2042-07-29

AI Technical Summary

Technical Problem

Graphite electrodes are prone to oxidation and ablation at high temperatures, resulting in shortening of service life. Existing ceramic coatings such as TaC have poor thermal shock and fatigue relief performance, are prone to peeling, and the preparation method has high cost and low efficiency.

Method used

Magneto-controlled sputtering technology and Shuanghui plasma surface metallurgy technology are used to prepare Ta-TaxC-TaC composite coating, including Ta-TaxC transition layer, TaxC intermediate layer and TaC protective layer, alleviate thermal stress through gradient structure, improve binding strength and ablation resistance Antioxidant properties.

Benefits of technology

It achieves high bonding strength on the surface of graphite electrode, excellent ablation and oxidation resistance, extends service life and reduces preparation costs. The coating structure is tight and free of cracks, and is suitable for graphite electrodes and other carbon-based materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115404452B_ABST
    Figure CN115404452B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite coating for improving the surface performance of a carbon-based electrode, a graphite electrode and a preparation method. The composite coating of the present invention comprises a first transition layer, a second transition layer and a protective layer, the thickness of the composite coating is 15 to 35 μm, the first transition layer is a Ta layer with a thickness of 3 to 4 μm, and the second transition layer is a Ta layer with a thickness of 2 to 6 μm. x C layer, the protective layer is a TaC layer with a thickness of 10 to 20 μm, the Ta x The C layer is composed of Ta2C and TaC, wherein x is Ta in Ta x The molar ratio of elements in the C layer. The interface structure components of each layer of the composite coating prepared by the present invention change gradually. The outermost TaC layer has high purity, controllable thickness and good conductivity, and is the main protective layer; the Ta-Ta x The C two-layer transition structure has a high melting point and stable properties. It further enhances the membrane-substrate bonding strength while providing good protection for the internal graphite electrode, thereby greatly improving the bonding strength, anti-ablation and anti-oxidation properties of the entire coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a graphite electrode surface anti-ablation and anti-oxidation treatment technology, and in particular to a composite coating for improving the surface performance of a carbon-based electrode, a graphite electrode and a preparation method. Background Art

[0002] Graphite electrode refers to a high-temperature resistant graphite conductive material made of petroleum coke and asphalt coke as aggregates and coal tar as binder, which is made through raw material calcination, crushing and grinding, batching, kneading, molding, roasting, impregnation, graphitization and mechanical processing. It has the advantages of good conductivity, fast discharge speed and low density. However, as a kind of electrode material, ablation resistance is an important factor affecting its service life. The mass loss and volume ablation rate of graphite electrodes after discharge ablation are large. At the same time, graphite electrodes also have the disadvantage of being easily oxidized at high temperatures. As the temperature rises, the carbon-oxygen reaction will continue to intensify, which may cause the graphite surface structure to become loose and fall off. This makes improving the ablation and oxidation resistance of the graphite electrode surface one of the urgent problems to be solved in the semiconductor field.

[0003] At present, the most common and widespread method for improving the surface performance of graphite electrodes is the external coating method, which forms a protective layer on the surface of the graphite electrode. The external coating method can effectively improve the anti-ablation and anti-oxidation properties of graphite electrodes, and mainly includes metal coatings, glass coatings, ceramic coatings, etc. Among them, ceramic coatings are more commonly used because ceramic coatings are easier to form than other coatings, the coating thickness is more controllable, and the electrical and thermal conductivity are closely combined. Commonly used ceramic coatings include SiC, boron glass, ZrC, HfC, TaC, etc., all of which have the ability to improve the anti-ablation and anti-oxidation of graphite electrodes.

[0004] Among them, TaC can not only maintain good mechanical properties above 3000℃, but also has good anti-ablation and anti-oxidation properties, stable high-temperature mechanical properties, good high-temperature chemical corrosion resistance, high hardness, good electrical conductivity, large thermal conductivity, good chemical compatibility and mechanical compatibility with carbon-based materials. It can be used as a protective coating for graphite electrodes to improve their anti-ablation and anti-oxidation properties. However, as a ceramic coating, TaC has poor plastic deformation ability, is sensitive to stress and cracks, has poor thermal shock resistance and fatigue relief properties, and has a large difference in thermal expansion coefficient from graphite electrodes, making it easy for the coating to peel off. In order to solve the thermal mismatch problem between the coating and the substrate, a second phase is often introduced or an intermediate layer is added to form a gradient composition structure between the coating and the substrate to buffer thermal stress, improve plastic deformation ability, and avoid cracks and peeling. Ta and Ta2C have better ductility than TaC, and their thermal expansion coefficient is between that of graphite electrode materials and TaC. As an intermediate layer, they can improve the thermal shock resistance of the coating, buffer thermal stress, alleviate deformation layer by layer, avoid cracks and peeling of the coating, and ensure a close bond between the coating and the substrate.

[0005] There are three main methods for preparing ceramic coatings such as TaC: solid phase method, liquid phase method, and gas phase method. Solid phase methods include reduction method, chemical method, etc.; liquid phase methods include molten salt method, sol-gel method, slurry-sintering method, plasma spraying method, etc.; gas phase methods include chemical vapor deposition CVD, physical vapor deposition PVD, chemical vapor infiltration CVI, etc. Different methods have different advantages and disadvantages. For example, the raw materials of the molten salt method are easy to obtain and the reaction temperature is low, but it is difficult to achieve selective coating on the surface of the workpiece; the spraying method has a simple process and good coating bonding, but the coating is prone to defects such as pores and cracks, and the coating is easy to oxidize; the density and purity of the CVD coating are controllable, and complex workpieces can be coated, but the equipment performance requirements are strict, the deposition rate is low, and the cycle is long; the PVD method has uniform and fine particles and dense coatings, but the experimental conditions are high and the preparation cost is high.

[0006] With the rapid development of the semiconductor field, higher requirements are placed on the performance and service life of electrode materials such as graphite electrodes. Therefore, it is of great significance to the development of semiconductor graphite electrodes to modify the surface of graphite electrodes to resist ablation and oxidation and to improve the service life of graphite electrodes. Summary of the invention

[0007] Purpose of the invention: The technical problem to be solved by the present invention is to provide a Ta-Ta that can be used for carbon-based electrodes. x C-TaC composite coating, the composite coating includes Ta coating, Ta x The present invention also provides a Ta-Ta x C-TaC composite coating graphite electrode and preparation method. The present invention adopts magnetron sputtering technology and double glow plasma surface metallurgy technology to prepare the coating, and sequentially prepares a Ta layer as the first transition layer, a Ta layer as the second transition layer, and a Ta layer as the third transition layer on the graphite electrode. x C (Ta2C+TaC) intermediate layer was used as the second transition layer and TaC protective layer to successfully prepare a composite coating with high bonding strength, excellent anti-ablation and anti-oxidation properties on the surface of the graphite electrode.

[0008] Technical solution: The composite coating for improving the surface performance of a carbon-based electrode according to the present invention comprises a first transition layer, a second transition layer and a protective layer. The thickness of the composite coating is 15 to 35 μm, the first transition layer is a Ta layer with a thickness of 3 to 4 μm, and the second transition layer is a Ta layer with a thickness of 2 to 6 μm. x C layer, the protective layer is a TaC layer with a thickness of 10 to 20 μm, the Ta x The C layer is composed of Ta2C and TaC, wherein x is Ta in Ta x The molar ratio of elements in layer C. In the present invention, the value of x ranges from 1 to 2.

[0009] The present invention adopts magnetron sputtering technology and double glow plasma surface metallurgy technology to sequentially prepare Ta first transition layer, Ta x C (Ta2C+TaC) second transition layer and TaC protective layer, successfully prepared Ta-Ta x C-TaC composite coating, which has high bonding strength, excellent anti-ablation performance and anti-oxidation performance.

[0010] The present invention Ta-Ta x C-TaC composite coating structure, total thickness is 15 ~ 35μm, including Ta-Ta x C gradient layer 5~10μm (including Ta x C layer 3 ~ 5μm), TaC protective layer 10 ~ 20μm. The mechanical properties of Ta and Ta2C are between those of graphite electrode materials and TaC, and they have good plasticity. x C (Ta2C + TaC) as the intermediate gradient layer can form a structure with plasticity and gradient distribution of thermal expansion coefficient, relieve deformation layer by layer to buffer thermal stress, improve the thermal shock resistance of the coating, and avoid cracking or peeling of the coating. TaC has excellent anti-ablation and anti-oxidation capabilities. Using TaC as a protective layer can reduce the ablation damage of the graphite electrode and block the diffusion of oxygen into the substrate. Such a multi-layer composite coating structure not only effectively protects the graphite electrode, but also ensures the integrity of the outer protective layer and the close bonding between the substrate and the coating.

[0011] As a preferred embodiment of the present invention, the first transition layer is prepared by a magnetron sputtering method, and the preparation parameters are: sputtering temperature is 200-300° C., sputtering power is 80-120 W, and sputtering time is 1.5-2.5 h.

[0012] As a preferred embodiment of the present invention, the second transition layer is prepared by double glow plasma surface metallurgy, and the preparation parameters are: the workpiece cathode voltage is 250-350V, the cathode current is 0.2-0.3A, the target source voltage is 550-650V, the source current is 2.5-3A, and the insulation time is 1.5-2.5h.

[0013] As a preferred embodiment of the present invention, the protective layer is prepared by double glow plasma surface metallurgy, and the preparation parameters are: the workpiece cathode voltage is 400-500V, the cathode current is 0.25-0.35A, the target source voltage is 800-900V, the source current is 2.5-3A, and the insulation time is 3-5h.

[0014] The method for preparing the composite coating of the present invention comprises the following steps:

[0015] (S11) depositing a Ta layer on the surface of the carbon-based electrode by a magnetron sputtering method: the sputtering temperature is 200 to 300° C., the sputtering power is 80 to 120 W, and the sputtering time is 1.5 to 2.5 h;

[0016] (S12) using the material obtained in step (S11) as the workpiece electrode and the C target material as the source electrode, preparing a second transition layer by double glow plasma surface metallurgy, wherein the preparation parameters are: the workpiece cathode voltage is 250-350V, the cathode current is 0.2-0.3A, the target source voltage is 550-650V, the source current is 2.5-3A, and the holding time is 1.5-2.5h;

[0017] (S13) Using the material obtained in step (S12) as the workpiece electrode and the TaC target as the source electrode, a protective layer is prepared by double glow plasma surface metallurgy. The preparation parameters are: the workpiece cathode voltage is 400-500V, the cathode current is 0.25-0.35A, the target source voltage is 800-900V, the source current is 2.5-3A, and the insulation time is 3-5h.

[0018] The present invention also provides a carbon-based electrode having the composite coating.

[0019] Furthermore, the carbon-based electrode is a graphite electrode, and the above-mentioned composite coating is deposited on the surface of the graphite electrode.

[0020] The present invention adopts a process combining magnetron sputtering technology and double glow plasma surface metallurgy technology to prepare a composite coating, giving full play to the characteristics of the two technologies and realizing the modification of the graphite electrode surface. Double glow plasma surface metallurgy technology is a surface coating technology that uses the double-layer glow discharge phenomenon of gas and the low-temperature plasma generated by the discharge under low vacuum conditions to form a diffusion layer with special physical and chemical properties on the surface of the substrate through ion bombardment, sputtering, space transmission, deposition and diffusion. It has the advantages of high target material utilization, fast penetration speed, high bonding strength, etc.

[0021] The method for preparing the graphite electrode of the present invention comprises the following steps:

[0022] (S21) loading a graphite electrode substrate and a Ta target into a chamber of a magnetron sputtering furnace, using the graphite electrode as an anode and a high-purity Ta target as a cathode, with a target-substrate distance of 30 to 50 mm, introducing argon gas, maintaining a working gas pressure of 0.45 to 0.55 Pa, a sputtering temperature of 200 to 300° C., a sputtering power of 80 to 120 W, and a sputtering time of 1.5 to 2.5 h, to complete the deposition of a Ta layer on the surface of the graphite electrode;

[0023] (S22) The graphite electrode on which the Ta layer has been deposited and the C target are placed in a double glow plasma surface metallurgical infiltration furnace, the vacuum degree is 0.1-0.2 Pa, argon gas is introduced, the working pressure is maintained at 30-40 Pa, the cathode voltage of the workpiece is 250-350 V, the cathode current is 0.2-0.3 A, the source voltage of the target is 550-650 V, the source current is 2.5-3 A, the holding time is 1.5-2.5 h, and the in-situ synthesis of Ta on the Ta surface is completed. x The C layer serves as the second transition layer;

[0024] (S23) The graphite electrode on which the second transition layer has been deposited and the TaC target are loaded into a double glow plasma surface metallurgical infiltration furnace, the vacuum degree is 0.1-0.2Pa, argon gas is introduced, the working gas pressure is maintained at 30-40Pa, the workpiece cathode voltage is 400-500V, the cathode current is 0.25-0.35A, the target source voltage is 800-900V, the source current is 2.5-3A, the insulation time is 3-5h, and the deposition of the TaC layer is completed.

[0025] As a preferred embodiment of the present invention, in step (S21), the graphite electrode is placed at the cathode in the vacuum chamber of the double glow furnace, the cathode voltage is set to 250-350V, and the substrate is bombarded with argon ions under heating conditions to remove impurities for 1-2 hours.

[0026] As a preferred embodiment of the present invention, the graphite electrode is prepared by the following steps:

[0027] Step 1: Clean the substrate and target;

[0028] The surfaces of the graphite electrode substrate, Ta target, C target and TaC target are polished with sandpaper, and the sandpaper is used to polish to 1000#~1200# in sequence, and then the sample is polished, and finally cleaned with an ultrasonic cleaning machine and dried. The cleaning agent is ethanol and acetone with a volume ratio of 3:1~5:1, wherein the graphite electrode is an HP high-power graphite electrode, the Ta target is a 99.99% high-purity target, the C target is a 99.999% high-purity target, and the TaC target is a 99.9% high-purity target;

[0029] Step 2: Remove impurities from the surface of the substrate;

[0030] The cleaned graphite electrode substrate is placed at the cathode in the vacuum chamber of the double glow furnace, the cathode voltage is set to 250-350V, and the substrate is bombarded with argon ions under heating conditions to remove impurities for 1-2 hours;

[0031] Step 3: Depositing the Ta layer using magnetron sputtering technology;

[0032] (1) The first step: loading the graphite electrode and Ta target into the chamber of the magnetron sputtering furnace, with the graphite electrode as the anode and the high-purity Ta target as the cathode, and adjusting the target-substrate distance to 20-40 mm;

[0033] (2) Step 2: The magnetron sputtering chamber is evacuated to a vacuum degree of 0.01-0.03 Pa, and argon gas is introduced with a purity of 99.999%, and the working pressure is maintained at 0.45-0.55 Pa;

[0034] (3) Step 3: Turn on the heating power, control the sputtering temperature at 200-300°C, the sputtering power at 80-120W, and the sputtering time at 1.5-2.5h;

[0035] (4) Step 4: Stop sputtering, turn off the power, cool down, and complete the deposition of Ta on the surface of the graphite electrode;

[0036] Step 4: Preparation of Ta using double glow plasma surface metallurgy technology x C (Ta2C+TaC) layer;

[0037] (1) The first step: the graphite electrode on which Ta has been deposited and the C target are placed in a double glow plasma surface metallurgical infiltration furnace, wherein the graphite electrode material on which Ta has been deposited is used as the cathode of the workpiece, and the high-purity C target is used as the source, and the distance between the two electrodes is adjusted to 8-12 mm;

[0038] (2) The second step: the double glow furnace chamber is evacuated to a vacuum degree of 0.1-0.2 Pa, argon gas is introduced, the purity of argon gas is 99.999%, and the working pressure is maintained at 30-40 Pa;

[0039] (3) Step 3: Set the working voltage of the two electrodes, the cathode voltage of the workpiece is 250-350 V, the cathode current is 0.2-0.3 A, the source voltage of the target is 550-650 V, the source current is 2.5-3 A, and the holding time is 1.5-2.5 h. The shorter time is selected to prevent the accumulation of C on the surface of the Ta layer and affect the preparation of the gradient coating;

[0040] (4) Step 4: Stop C infiltration, turn off power, cool down, and complete the C infiltration on the substrate surface and generate Ta x C(Ta2C+TaC);

[0041] Step 5: Prepare TaC protective layer by double glow plasma surface metallurgy technology;

[0042] (1) Step 1: deposit Ta x The graphite electrode of the C layer and the TaC target are loaded into a double glow plasma surface metallurgical infiltration furnace, wherein the graphite electrode with the second transition layer deposited is used as the cathode of the workpiece, and the high-purity TaC target is used as the source, and the distance between the two electrodes is adjusted to 10-20 mm;

[0043] (2) The second step: the double glow furnace chamber is evacuated to a vacuum degree of 0.1-0.2 Pa, argon gas is introduced, and the working pressure is maintained at 30-40 Pa;

[0044] (3) Step 3: Set the working voltage of the two electrodes, the cathode voltage of the workpiece is 400-500 V, the cathode current is 0.25-0.35 A, the source voltage of the target is 800-900 V, the source current is 2.5-3 A, and the holding time is 3-5 h;

[0045] (4) Step 4: Stop deposition, turn off power, cool, and complete the deposition of TaC on the surface of the gradient layer.

[0046] In the preparation method of the present invention, step 2 uses pre-sputtering to remove impurities from the surface of the graphite substrate, so that in the subsequent coating preparation, the coating and the substrate are easier to combine, more uniform and dense, and the integrity of the coating is avoided from being affected by impurities on the substrate surface.

[0047] Beneficial effects: (1) The present invention establishes a gradient composite coating structure Ta-Ta x C-TaC can not only play their respective advantages, but also make up for each other's shortcomings. TaC coating has very high hardness, high temperature strength, good oxidation resistance and ablation resistance, but when TaC is used as a surface modification layer, its plasticity is low and its thermal shock resistance is poor, which makes the interface bonding strength low. The mechanical properties and thermal expansion coefficients of Ta and Ta2C are between those of graphite electrode and TaC. Ta and Ta2C can be used as intermediate transition layers. In the composite gradient coating structure, Ta, Ta x The Ta2C+TaC transition layer can greatly improve the thermal mismatch problem between the substrate and the coating, improve the thermal shock resistance of the coating, buffer the thermal stress, and alleviate the cracks and coating peeling caused by deformation, thereby ensuring a close bond between the coating and the substrate; at the same time, it also provides a certain degree of protection for the internal graphite electrode. The main function of the TaC conductive ceramic layer is to protect the graphite electrode from ablation damage and oxidative decomposition during discharge, thereby improving its ablation resistance and oxidation resistance. The Ta-Ta x The C-TaC composite coating has good integrity and high density; (2) the coating of the present invention is tightly bonded to the substrate, the mechanical properties are gradiently distributed, and the thermal shock resistance and plastic deformation resistance are good; (3) the outer surface of the coating of the present invention is uniform and dense, without cracks, thus avoiding the thermal mismatch problem between the coating and the substrate; (4) the coating of the present invention has excellent performance, strong ablation resistance and oxidation resistance; (5) the target material of the present invention has a high utilization rate, saving resource costs. In addition, the present invention uses the double glow technology to deposit the coating at a fast speed; (6) the multi-layer composite coating structure of the present invention has a wide range of uses, not only suitable for graphite electrodes, but also can be applied to other carbon-based materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 The Ta-Ta x Schematic diagram of the C-TaC coating structure; in the figure: (a) is the graphite electrode, (b) is the Ta layer, and (c) is the Ta x C layer, (d) is TaC protective layer;

[0049] Figure 2 This is a SEM image of the graphite electrode and composite coating prepared in Example 2;

[0050] Figure 3 It is a schematic structural diagram of the double glow plasma surface metallurgy equipment in an embodiment of the present invention. DETAILED DESCRIPTION

[0051] Embodiment 1: This embodiment is implemented under the following implementation conditions and technical requirements:

[0052] First, the surfaces of the graphite electrode substrate, Ta target, C target and TaC target were polished with sandpaper to 1000# and polished, and ultrasonic cleaning was performed with a cleaning agent of ethanol:acetone=3:1 (V:V), and the surfaces were dried for standby use, wherein the graphite electrode was an HP high-power graphite electrode, the Ta target was a 99.99% high-purity target, the C target was a 99.999% high-purity target, and the TaC target was a 99.9% high-purity target;

[0053] Secondly, place the graphite electrode substrate at the cathode in the vacuum chamber of the double glow furnace, turn on the mechanical pump to evacuate to a vacuum degree of 0.1Pa, introduce argon gas, maintain the working gas pressure at 30Pa, turn on the cathode power supply and set the cathode voltage to 250V, and the working time is 1h;

[0054] Then, a Ta layer was deposited as the first transition layer by magnetron sputtering. The graphite electrode material and the Ta target were loaded into a magnetron sputtering furnace, with the substrate as the anode and the target as the cathode. The target-substrate distance was 20 mm. The vacuum was evacuated to a pressure of 0.01 Pa, and argon gas was introduced to maintain the working pressure at 0.45 Pa. The heating power was turned on, the sputtering temperature was controlled at 200 ° C, the sputtering power was 60 W, and the sputtering time was 1.5 h.

[0055] Next, Ta was prepared by double glow plasma surface metallurgy. x C is used as the second transition layer. The graphite electrode on which Ta has been deposited and the C target are placed in a double glow plasma surface metallurgical furnace, with the substrate as the workpiece cathode, the target as the source, and the distance between the two electrodes being 10 mm. The mechanical pump is turned on to evacuate to a vacuum degree of 0.1 Pa, and argon gas is introduced with a purity of 99.999%. The working gas pressure is maintained at 30 Pa, and the two-pole power supply is turned on and the workpiece cathode voltage is set to 250 V, the cathode current to 0.2 A, the target source voltage to 550 V, the source power supply to 2.5 A, and the holding time to 1.5 h.

[0056] Finally, the TaC protective layer was prepared by the double glow plasma surface metallurgy method. The graphite electrode and TaC target with the second transition layer deposited were loaded into the double glow plasma surface metallurgy furnace, with the substrate as the workpiece cathode and the target as the source. The distance between the two electrodes was 10 mm. The mechanical pump was turned on to evacuate to a vacuum degree of 0.1 Pa, and argon gas was introduced with a purity of 99.999%. The working gas pressure was maintained at 30 Pa. The two-pole power supply was turned on and the workpiece cathode voltage was set to 400 V, the cathode current to 0.25 A, the target source voltage to 800 V, the source power supply to 2.5 A, and the insulation time to 3 hours.

[0057] The prepared Ta-Ta x The structure of the C-TaC composite coating was observed. It can be seen that the coating structure is uniform and dense, there is no crack on the surface, and it is well bonded to the substrate. The total thickness of the coating is 16μm, of which Ta-Ta x The C gradient layer is 5 μm (Ta x C layer is 2μm), and the TaC protective layer is 11μm.

[0058] The hardness of the graphite electrode material was tested and the surface hardness was 2103HV.

[0059] Electrode ablation experiments were conducted on graphite electrode materials. Under N2 atmosphere, the total transferred charge was maintained at 500C. The ablation rate of the graphite electrode material was 32.8μg / C when the single pulse transferred charge was 1.5C, and the surface ablation was relatively slight.

[0060] The graphite electrode material was subjected to an oxidation test. The test sample was placed in a high-temperature oxygen environment at 800°C to 900°C, kept warm for 6 hours, and then cooled and taken out. The mass difference of the graphite electrode before and after oxidation was measured, and the high-temperature oxidation weight loss rate was calculated to be 6.71%.

[0061] Embodiment 2: This embodiment is implemented under the following implementation conditions and technical requirements:

[0062] First, the surfaces of the graphite electrode substrate, Ta target, C target and TaC target were polished with sandpaper to 1100# and polished, and ultrasonic cleaning was performed with a cleaning agent of ethanol:acetone=4:1 (V / V), and then dried for use, wherein the graphite electrode was an HP high-power graphite electrode, the Ta target was a 99.99% high-purity target, the C target was a 99.999% high-purity target, and the TaC target was a 99.9% high-purity target;

[0063] Secondly, place the graphite electrode substrate at the cathode in the vacuum chamber of the double glow furnace, turn on the mechanical pump to evacuate to a vacuum degree of 0.2Pa, introduce argon gas, maintain the working gas pressure at 35Pa, turn on the cathode power supply and set the cathode voltage to 200V, and the working time is 1.5h;

[0064] Then, a Ta layer was deposited as the first transition layer by magnetron sputtering. The graphite electrode material and Ta target were loaded into a magnetron sputtering furnace, with the substrate as the anode and the target as the cathode. The target-substrate distance was 30 mm. The furnace was evacuated to a pressure of 0.02 Pa, and argon gas was introduced to maintain the working pressure at 0.5 Pa. The heating power was turned on, the sputtering temperature was controlled at 250°C, the sputtering power was 80 W, and the sputtering time was 2 hours.

[0065] Next, Ta was prepared by double glow plasma surface metallurgy. x C is used as the second transition layer. The graphite electrode on which Ta has been deposited and the C target are placed in a double glow plasma surface metallurgical furnace, with the substrate as the workpiece cathode and the target as the source. The distance between the two electrodes is 15 mm. The mechanical pump is turned on to evacuate to a vacuum degree of 0.15 Pa, and argon gas is introduced with a purity of 99.999%. The working gas pressure is maintained at 35 Pa. The two-pole power supply is turned on and the workpiece cathode voltage is set to 300 V, the cathode current to 0.25 A, the target source voltage to 600 V, the source power supply to 2.75 A, and the insulation time to 2 hours.

[0066] Finally, the TaC protective layer was prepared by the double glow plasma surface metallurgy method. The graphite electrode material and TaC target with the second transition layer deposited were loaded into the double glow plasma surface metallurgy furnace, the substrate was the workpiece cathode, the target material was the source, the distance between the two electrodes was 15mm, the mechanical pump was turned on to evacuate to a vacuum degree of 0.15Pa, argon gas was introduced, the purity of argon gas was 99.999%, the working pressure was maintained at 35Pa, the two-pole power supply was turned on and the workpiece cathode voltage was set to 450V, the cathode current was 0.3A, the target source voltage was 850V, the source power supply was 2.75A, and the insulation time was 4h.

[0067] The structure of the Ta-TaC composite coating prepared was observed. It can be seen that the coating has a uniform and dense structure, no cracks on the surface, and good bonding with the substrate. The total thickness of the coating is 22 μm, of which Ta-Ta x The C gradient layer is 7 μm (Ta x C layer is 3μm), TaC protective layer is 15μm, and the SEM image of the prepared sample is as follows Figure 2 shown.

[0068] The hardness of the graphite electrode material was tested and the surface hardness was 2155HV.

[0069] Electrode ablation experiments were conducted on graphite electrode materials. Under N2 atmosphere, the total transferred charge was maintained at 500C. The ablation rate of the graphite electrode material was 23.6μg / C when the single pulse transferred charge was 1.5C, and the surface ablation was slight.

[0070] The graphite electrode material was subjected to an oxidation test. The test sample was placed in a high-temperature oxygen environment of 800°C to 900°C, kept warm for 6 hours, and then cooled and taken out. The mass difference of the graphite electrode before and after oxidation was measured, and the high-temperature oxidation weight loss rate was calculated to be 3.83%.

[0071] Embodiment 3: This embodiment is implemented under the following implementation conditions and technical requirements:

[0072] First, the surfaces of the graphite electrode substrate, Ta target, C target and TaC target were polished with sandpaper to 1200# and polished, and ultrasonic cleaning was performed with a cleaning agent of ethanol:acetone=5:1, and the surfaces were dried for standby use, wherein the graphite electrode was an HP high-power graphite electrode, the Ta target was a 99.99% high-purity target, the C target was a 99.999% high-purity target, and the TaC target was a 99.9% high-purity target;

[0073] Secondly, place the graphite electrode substrate at the cathode in the vacuum chamber of the double glow furnace, turn on the mechanical pump to evacuate to a vacuum degree of 0.2Pa, introduce argon gas, maintain the working gas pressure at 40Pa, turn on the cathode power supply and set the cathode voltage to 350V, and the working time is 2h;

[0074] Then, a Ta layer was deposited as the second transition layer by magnetron sputtering. The graphite electrode material and the Ta target were loaded into a magnetron sputtering furnace, with the substrate as the anode and the target as the cathode. The target-substrate distance was 40 mm. The vacuum was evacuated to a pressure of 0.03 Pa, and argon gas was introduced to maintain the working pressure at 0.55 Pa. The heating power was turned on, the sputtering temperature was controlled at 300 ° C, the sputtering power was 100 W, and the sputtering time was 2.5 h.

[0075] Next, Ta was prepared by double glow plasma surface metallurgy. x C is used as the second transition layer. The graphite electrode on which Ta has been deposited and the C target are placed in a double glow plasma surface metallurgical furnace, with the substrate as the workpiece cathode and the target as the source. The distance between the two electrodes is 20 mm. The mechanical pump is turned on to evacuate to a vacuum degree of 0.2 Pa, and argon gas is introduced with a purity of 99.999%. The working gas pressure is maintained at 40 Pa. The two-pole power supply is turned on and the workpiece cathode voltage is set to 350 V, the cathode current to 0.3 A, the target source voltage to 650 V, the source power supply to 3 A, and the holding time to 2.5 h.

[0076] Finally, the TaC protective layer was prepared by the double glow plasma surface metallurgy method. The graphite electrode material and TaC target with the second transition layer deposited were loaded into the double glow plasma surface metallurgy furnace, the substrate was the workpiece cathode, the target material was the source, the distance between the two electrodes was 20mm, the mechanical pump was turned on to evacuate to a vacuum degree of 0.2Pa, argon gas was introduced, the purity of argon gas was 99.999%, the working pressure was maintained at 40Pa, the two-pole power supply was turned on and the workpiece cathode voltage was set to 500V, the cathode current was 0.35A, the target source voltage was set to 900V, the source power supply was set to 3A, and the insulation time was 5h.

[0077] The structure of the Ta-TaC composite coating prepared was observed. It can be seen that the coating has a uniform and dense structure, no cracks on the surface, and good bonding with the substrate. The total thickness of the coating is 29 μm, of which Ta-Ta x The C gradient layer is 10 μm (including Ta x C layer is 6μm), and the TaC protective layer is 19μm.

[0078] The hardness of the graphite electrode material was tested and the surface hardness was 2212HV.

[0079] Electrode ablation experiments were conducted on graphite electrode materials. Under N2 atmosphere, the total transferred charge was maintained at 500C. The ablation rate of the graphite electrode material was 29.3μg / C when the single pulse transferred charge was 1.5C, and the surface ablation was relatively slight.

[0080] The graphite electrode material was subjected to an oxidation test. The test sample was placed in a high-temperature oxygen environment of 800°C to 900°C, kept at this temperature for 6 hours, and then cooled and taken out. The mass difference of the graphite electrode before and after oxidation was measured, and the high-temperature oxidation weight loss rate was calculated to be 5.14%;

[0081] Comparative Example 1: This comparative example (pure graphite electrode) was carried out under the following experimental conditions and technical requirements:

[0082] The surface of the graphite electrode was ground with sandpaper to 1000# and polished, ultrasonically cleaned with a cleaning agent of ethanol:acetone=3:1, and dried for later use. The graphite electrode was a HP high-power graphite electrode.

[0083] The hardness of the graphite electrode material was tested and the surface hardness was 426HV.

[0084] An electrode ablation experiment was carried out on the graphite electrode material. Under N2 atmosphere, the total transferred charge was maintained at 500C. The ablation rate of the graphite electrode material was 107.1μg / C when the single pulse transferred charge was 1.5C, and the surface ablation was severe.

[0085] The graphite electrode material was subjected to an oxidation test. The test sample was placed in a high-temperature oxygen environment at 800°C to 900°C, kept warm for 6 hours, and then cooled and taken out. The mass difference of the graphite electrode before and after oxidation was measured, and the high-temperature oxidation weight loss rate was calculated to be 19.52%.

[0086] Comparative Example 2: This comparative example (pure TaC coating) was carried out under the following experimental conditions and technical requirements:

[0087] First, the graphite electrode substrate and the TaC target surface were polished with sandpaper to 1000# and then polished, and ultrasonic cleaning was performed with a cleaning agent of ethanol:acetone=3:1, and then dried for use, wherein the graphite electrode was a HP high-power graphite electrode and the TaC target was a 99.9% high-purity target;

[0088] Then, the graphite electrode substrate was placed at the cathode in the vacuum chamber of the double glow furnace, the mechanical pump was turned on to evacuate to a vacuum degree of 0.1 Pa, argon gas was introduced, the working gas pressure was maintained at 30 Pa, the cathode power supply was turned on and the cathode voltage was set to 250 V, and the working time was 1 h;

[0089] Finally, the TaC protective layer was prepared by the double glow plasma surface metallurgy method. The graphite electrode and TaC target were loaded into the double glow plasma surface metallurgy furnace, the substrate was the workpiece cathode, the target was the source, the distance between the two electrodes was 15mm, the mechanical pump was turned on to evacuate to a vacuum degree of 0.15Pa, argon gas was introduced, the purity of argon gas was 99.999%, the working pressure was maintained at 35Pa, the two-pole power supply was turned on and the workpiece cathode voltage was set to 450V, the cathode current was 0.3A, the target source voltage was 850V, the source power supply was 2.75A, and the insulation time was 4h; the structure of the prepared TaC coating was observed, and a small amount of cracks were observed on the coating surface, and the coating thickness was 14μm.

[0090] The hardness of the graphite electrode material was tested and the surface hardness was 2147HV.

[0091] Electrode ablation experiments were conducted on graphite electrode materials. Under N2 atmosphere, the total transferred charge was maintained at 500C, and the ablation rate of the graphite electrode material was 51.2μg / C when the single pulse transferred charge was 1.5C.

[0092] The graphite electrode material was subjected to an oxidation test. The test sample was placed in a high-temperature oxygen environment of 800°C to 900°C, kept warm for 6 hours, and then cooled and taken out. The mass difference of the graphite electrode before and after oxidation was measured, and the high-temperature oxidation weight loss rate was calculated to be 10.16%.

[0093] The test results of the embodiments and comparative examples are shown in Table 1:

[0094] Table 1 Performance test results of samples prepared in Examples 1-3 and Comparative Examples 1-2

[0095]

Claims

1. A composite coating for improving the surface performance of a carbon-based electrode, characterized in that: The composite coating includes a first transition layer, a second transition layer and a protective layer. The thickness of the composite coating is 15-35 μm. The first transition layer is a Ta layer with a thickness of 3-4 μm, and the second transition layer is a Ta layer with a thickness of 2-6 μm. x C layer, the protective layer is a TaC layer with a thickness of 10-20 μm, the Ta x The C layer is composed of Ta2C and TaC, wherein x is Ta in Ta x The molar ratio of elements in the C layer; The preparation method of the composite coating comprises the following steps: (S11) depositing a Ta layer on the surface of the carbon-based electrode by a magnetron sputtering method: the sputtering temperature is 200-300°C, the sputtering power is 80-120W, and the sputtering time is 1.5-2.5h; (S12) using the material obtained in step (S11) as the workpiece electrode and the C target material as the source electrode, preparing a second transition layer by double glow plasma surface metallurgy, wherein the preparation parameters are: the workpiece cathode voltage is 250-350 V, the cathode current is 0.2-0.3 A, the target source voltage is 550-650 V, the source current is 2.5-3 A, and the holding time is 1.5-2.5 h; (S13) Using the material obtained in step (S12) as the workpiece electrode and the TaC target as the source electrode, a protective layer is prepared by double glow plasma surface metallurgy, and the preparation parameters are: the workpiece cathode voltage is 400~500V, the cathode current is 0.25~0.35A, the target source voltage is 800~900V, the source current is 2.5~3A, and the insulation time is 3~5h.

2. A method for preparing a composite coating according to claim 1, characterized in that: The following steps are involved: (S11) depositing a Ta layer on the surface of the carbon-based electrode by a magnetron sputtering method: the sputtering temperature is 200-300°C, the sputtering power is 80-120W, and the sputtering time is 1.5-2.5h; (S12) using the material obtained in step (S11) as the workpiece electrode and the C target material as the source electrode, preparing a second transition layer by double glow plasma surface metallurgy, wherein the preparation parameters are: the workpiece cathode voltage is 250-350 V, the cathode current is 0.2-0.3 A, the target source voltage is 550-650 V, the source current is 2.5-3 A, and the holding time is 1.5-2.5 h; (S13) Using the material obtained in step (S12) as the workpiece electrode and the TaC target as the source electrode, a protective layer is prepared by double glow plasma surface metallurgy, and the preparation parameters are: the workpiece cathode voltage is 400~500V, the cathode current is 0.25~0.35A, the target source voltage is 800~900V, the source current is 2.5~3A, and the insulation time is 3~5h.

3. A carbon-based electrode having the composite coating as claimed in claim 1.

4. A graphite electrode, characterized in that: The composite coating as claimed in claim 1 is deposited on the surface of the graphite electrode.

5. The method for preparing a graphite electrode according to claim 4, characterized in that: The following steps are involved: (S21) loading a graphite electrode substrate and a Ta target into a chamber of a magnetron sputtering furnace, using the graphite electrode as an anode and a high-purity Ta target as a cathode, with a target-substrate distance of 30-50 mm, introducing argon gas, maintaining a working gas pressure of 0.45-0.55 Pa, a sputtering temperature of 200-300° C., a sputtering power of 80-120 W, and a sputtering time of 1.5-2.5 h, to complete the deposition of a Ta layer on the surface of the graphite electrode; (S22) The graphite electrode and C target material on which the Ta layer has been deposited are placed in a double glow plasma surface metallurgical infiltration furnace, the vacuum degree is 0.1~0.2Pa, argon gas is introduced, the working pressure is maintained at 30~40Pa, the cathode voltage of the workpiece is 250~350V, the cathode current is 0.2~0.3A, the source voltage of the target material is 550~650V, the source current is 2.5~3A, the holding time is 1.5~2.5h, and the in-situ synthesis of Ta on the Ta surface is completed. x The C layer serves as the second transition layer; (S23) The graphite electrode on which the second transition layer has been deposited and the TaC target are placed in a double glow plasma surface metallurgical infiltration furnace with a vacuum degree of 0.1~0.2Pa. Argon is introduced to maintain the working gas pressure at 30~40Pa. The cathode voltage of the workpiece is 400~500V, the cathode current is 0.25~0.35A, the source voltage of the target is 800~900V, the source current is 2.5~3A, and the insulation time is 3~5h to complete the deposition of the TaC layer.

6. The method for preparing a graphite electrode according to claim 5, characterized in that: In step (S21), the graphite electrode is placed at the cathode in the vacuum chamber of the double glow furnace, the cathode voltage is set to 250-350V, and the substrate is bombarded with argon ions under heating conditions to remove impurities for 1-2 hours.

Citation Information

Patent Citations

  • Electrode for semiconductor manufacturing and method thereof

    KR1020090121008A

  • Tantalum Carbide-Coated Carbon Material and Production Method Thereof

    US20120040172A1